Environmental Stresses and Your Florida Lawn - Laurie Trenholm (EDIS)
Florida lawns are subject to many environmental stresses. These can include nutrient deficiency, salinity, temperature extremes, over- or under-watering, soil problems, and prolonged exposure to shade or traffic. The use of proper cultural practices will help keep your lawn healthy and more stress-tolerant. This revised 2-page fact sheet explains how to choose the most appropriate grass, fertilize properly, mow to the correct height, and irrigate for your lawn’s needs. Written by L.E. Trenholm, and published by the Environmental Horticulture Department, January 2016.